DETERMINING TIME SERIES DEMAND FORECASTING AND MATERIAL REQUIREMENT PLANNING FOR TUNA TOFU PRODUCT AT NIKMAT LESTARI COMPANY - Pertiwi, Kartika Cahya; Handayati, Yuanita (Journal of Business and Management, 2018)
Abstract. Forecasting plays important role in every business. Most of business decisions are made under the conditions of risk and uncertainty. A company could lessen the adverse effects of risky by determining the demand prospects for its products and services in the future. Same goes to inventory management. With good inventory management, it ensure that the materials would be available in sufficient quantity and at the proper time for production to happen. This research’s aim is to determine the appropriate demand forecasting system and material requirement planning for tuna tofu product of Nikmat Lestari Company. Nikmat Lestari Company is one of the pioneer of tuna tofu producers in Pacitan that already has their product shipped to Jakarta. For determine the appropriate demand forecasting system for Nikmat Lestari, the forecasting method used in the analysis involved Time Series Forecasting method. The forecasting method was checked using measurement of forecast error tools. After finding the appropriate forecasting method with lowest error, determine the appropriate material requirement for tuna tofu. The result of this research showed that Winter’s Model is the most suitable demand forecasting system for Nikmat Lestari Company because it produces the most accurate forecast result and least forecast error. For the material requirement planning, Lot-for-lot is the most suitable for Nikmat Lestari Company because it has lower cost compared to EOQ method.Keyword: demand forecasting, inventory management, Material Requirement Planning, Nikmat Lestari Company, tuna tofu